ANALISIS MATERI STRUKTUR ATOM DALAM BUKU TEKS PELAJARAN KIMIA SMA/MA KELAS X DARI PERSPEKTIF 4S TMD PADA TAHAP SELEKSI - Ramadhan, Mohamad Iqbal (2015)
Textbook is one of the teaching materials that most widely used by students and also influential on improving the quality of learning. This study was conducted to determine the achievement of criteria for instructional materials according to 4S TMD (4 Step Teaching Material Development) methods at the selection stage, on atomic structure section in 10th grade of high school textbooks chemistry (author of A publisher D) that most widely used in high school at Bandung. The research method in this study is descriptive qualitative method. There are three criteria for good teaching materials according to the 4S TMD methods. The first criterion is "Scope In Accordance with the Demands of Curriculum" that can be known by analyzing the immensity and profundity of the material. Based on analysis of the immensity of the material, it is known that the immensity of the atomic structure materials is not in accordance with the demands of the curriculum. This is because the atomic structure atom materials are delivered nine topics that are not required, and there is one less extensive knowledge expressed. Then based on the analysis of the profundity of the material, it is known that the profundity of the atomic structure of the material is also not in accordance with the demands of the curriculum. This is because there are two topics that are having high profundity in the atomic structure of materials. Furthermore, the second criterion is "Validity of the Concept", known by analyzing the validity of the concept. The results of this analysis indicate that not all of the concepts on the atomic structure materials scientifically correct. This is because there are two concepts that are improper. Finally, the third criterion is to instill the values, determined by analysis of value investment. Based on the analysis of value investment, discovered that there is one value embedded in the atomic structure materials which is "religious value". Keywords: Textbook, Atomic Structure, 4S TMD, Immensity and Profundity of Materials, Validity of Concept, Value Investment. Buku teks pelajaran adalah salah satu bentuk bahan ajar yang paling banyak digunakan siswa serta berpengaruh dalam meningkatkan kualitas suatu pembelajaran. Penelitian ini dilakukan untuk mengetahui ketercapaian kriteria bahan ajar yang baik menurut metode 4S TMD (4 Step Teaching Material Development) pada tahap seleksi, pada materi struktur atom dalam buku teks pelajaran kimia SMA/MA kelas X (penulis A penerbit D) yang paling banyak digunakan di SMA Negeri se-Kota Bandung. Metode penelitian dalam penelitian ini adalah metode deskriptif kualitatif. Terdapat tiga kriteria bahan ajar yang baik menurut metode 4S TMD. Kriteria pertama yakni kesesuaian dengan Kurikulum, kebenaran ilmiah, dan penanaman nilai-nilai (value). Hasilnya diketahui, bahwa keluasan materi struktur atom belum sesuai dengan tuntutan kurikulum. Hal ini dikarenakan dalam materi struktur atom disampaikan 9 topik yang tidak dituntut, serta terdapat 1 pengetahuan yang dinyatakan kurang luas. Kemudian berdasarkan analisis kedalaman materi, diketahui bahwa kedalaman materi struktur atom juga belum sesuai dengan tuntutan kurikulum. Hal ini dikarenakan terdapat 2 topik yang terlalu dalam pada materi struktur atom. Hasil analisis kriteria Kebenaran Konsep, diketahui dengan melakukan analisis kebenaran konsep. Hasil analisis ini menunjukkan bahwa belum semua konsep pada materi struktur atom benar secara keilmuan. Hal ini dikarenakan terdapat 2 konsep yang dinyatakan kurang tepat. Sedangkan kriteria penanaman nilai-nilai, diketahui dengan melakukan analisis penanaman nilai. Berdasarkan analisis penanaman nilai, ditemukan satu nilai yang ditanamkan pada materi struktur atom yaitu nilai religius. Kata kunci: Buku Teks Pelajaran, Struktur Atom, 4S TMD, Keluasan dan Kedalaman Materi, Kebenaran Konsep, Penanaman Nilai.